Peningkatan Komunikasi Matematika Siswa melalui Pendekatan Saintifik (Scientific) dengan Strategi TTW (Think Talk Write)(PTK Pembelajaran Matematika Kelas X TKJ 1 di SMK Negeri 1 Banyudono Tahun Ajaran 2014/2015) - Wulan, Rikhi; , Rita P. Khotimah, S.Si., M.Sc (2015)
Rikhi Wulan / A410112013. The Improvement Students' Mathematics Communication by applying Scientific Approach (Scientific) with TTW (Think Talk Write) Strategy(CAR mathematics Learning grade X TKJ 1 of Vocational High School1 ofBanyudonoyear 2014/2015). Thesis. Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta. July 2015. The aim of this research is to improve students'mathematics communication grade X TKJ 1 of vocational high school 1 of Banyudonoby applying scientific approach (scientific) with TTW (Think Talk Write) strategy in mathematics learning. This research is a classroom action research. Subjects recipient of action is class X TKJ 1 of vocational high school 1 ofBanyudono which amounts to 35 students. Methods of data collection are by observation, field notes, documentation and test. The technique of data analysis is done by three stages, namely data reduction, exposure data, and inference. Validity of the data is done by triangulation investigators and methods. Research data, showed an increase in mathematics communication that can be observed from the increase in the percentage of indicators, namely the ability of the student (1) express mathematical ideas by speaking from 14,29% to 74,29% (2) express mathematical ideas by writing from 17,14% to 74,29% (3) demonstrate and depict mathematical ideas visually from 14,29% to 71,43% (4) use mathematical notation to representideas, describe relationships and model situation from 20% to 82,86%. The conclusion of this research is the application of scientific approaches (scientific) with the TTW (Think Talk Write)strategycan improve mathematics communication.